Imperium Romanum Nation-State - Ciprian, Pater
This document articulates the foundational principles, legal frameworks, and strategic imperatives underpinning the establishment of Imperium Romanum a sovereign Digital Nation-State. It aims to provide a comprehensive analysis grounded in international relations, legal theory, economics, and historical prece- dents. The focus is on addressing the existential threats posed by blockchain technology, AI, social impact bonds, digital identification systems, and social engineering practices that collectively risk transforming individuals into un- witting digital subjects—a violation of international laws prohibiting unlawful imprisonment and forced labor. By asserting sovereignty over unclaimed territories such as Marie Byrd Land in Antarctica for research purposes, Imperium Romanum seeks to legitimize its physical presence in accordance with international law, including the Antarctic Treaty System. This document employs advanced legal argumentation, referenc- ing precedent cases and established legal theories, to advocate for the voluntary acceptance of citizenship within Imperium Romanum as a means to counteract the unstoppable technological innovations in Web3 and FinTech that threaten individual autonomy and liberty.